Naturally Occurring Stable Calcium Isotope Ratios in Body Compartments Provide a Novel Biomarker of Bone Mineral Balance in Children and Young Adults. (11th September 2020) - Shroff, Rukshana; Fewtrell, Mary; Heuser, Alexander; Kolevica, Ana; Lalayiannis, Alexander; McAlister, Louise; Silva, Selmy; Goodman, Nadine; Schmitt, Claus P; Biassoni, Lorenzo; Rahn, Anja; Fischer, Dagmar‐Christiane; et al.
ABSTRACT: Serum calcium (Ca), bone biomarkers, and radiological imaging do not allow accurate evaluation of bone mineral balance (BMB), a key determinant of bone mineral density (BMD) and fracture risk. We studied naturally occurring stable (non‐radioactive) Ca isotopes in different body pools as a potential biomarker of BMB. 42 Ca and 44 Ca are absorbed from our diet and sequestered into different body compartments following kinetic principles of isotope fractionation; isotopically light 42 Ca is preferentially incorporated into bone, whereas heavier 44 Ca preferentially remains in blood and is excreted in urine and feces. Their ratio (δ 44/42 Ca) in serum and urine increases during bone formation and decreases with bone resorption. In 117 healthy participants, we measured Ca isotopes, biomarkers, and BMD by dual‐energy X‐ray absorptiometry (DXA) and tibial peripheral quantitative CT (pQCT). 44 Ca and 42 Ca were measured by multi‐collector ionization‐coupled plasma mass‐spectrometry in serum, urine, and feces. The relationship between bone Ca gain and loss was calculated using a compartment model. δ 44/42 Caserum and δ 44/42 Caurine were higher in children ( n = 66, median age 13 years) compared with adults ( n = 51, median age 28 years; p < 0.0001 and p = 0.008, respectively). δ 44/42 Caserum increased with height in boys ( p < 0.001, R 2 = 0.65) and was greatest at Tanner stage 4. δ 44/42 Caserum correlated positively with biomarkers of bone formation (25‐hydroxyvitaminD [ p < 0.0001, R 2 = 0.37] and alkaline phosphatase [ p = 0.009, R 2 = 0.18]) and negatively with bone resorption marker parathyroid hormone (PTH; p = 0.03, R 2 = 0.13). δ 44/42 Caserum strongly positively correlated with tibial cortical BMD Z ‐score ( n = 62; p < 0.001, R 2 = 0.39) but not DXA. Independent predictors of tibial cortical BMD Z ‐score were δ 44/42 Caserum ( p = 0.004, β = 0.37), 25‐hydroxyvitaminD ( p = 0.04, β = 0.19) and PTH ( p = 0.03, β = −0.13), together predicting 76% of variability. In conclusion, naturally occurring Ca isotope ratios in different body compartments may provide a novel, non‐invasive method of assessing bone mineralization. Defining an accurate biomarker of BMB could form the basis of future studies investigating Ca dynamics in disease states and the impact of treatments that affect bone homeostasis. © 2020 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).